Relationship between reputational aspects of companies and their share price in the online environment - Rojas-de-Gracia, María Mercedes; Casado-Molina, Ana María; Alarcón-Urbistondo, María del Pilar (Elsevier, 2021)
Although the relationship between many reputational aspects of companies and their share price have received attention from researchers, most studies have been directly or indirectly based on opinions collected through surveys or interviews. This work provides evidence of the existence of such relationships in the online environment. This involved collecting opinions that, in general, are published spontaneously, come from a range of different audiences and represent a large volume of information. This study shows that a company's integrity of governance contributes significantly to the formation of its corporate reputation. This is of great importance since corporate reputation is one of the factors that financial analysts take into account when deciding whether or not to recommend investing in a company's shares. In turn, both the perception of a company's integrity and analysts' recommendations have an impact on share prices variations. La relación entre muchos aspectos reputacionales de las empresas y su cotización ha recibido la atención de los investigadores. La mayoría de los estudios se han basado en opiniones recogidas a través de encuestas o entrevistas. Este trabajo aporta evidencia de la existencia de dichas relaciones en el entorno online. Este estudio demuestra que la integridad de la gobernanza de una empresa contribuye significativamente a la formación de su reputación corporativa. Esto es de gran importancia ya que la reputación corporativa es uno de los factores que los analistas financieros tienen en cuenta a la hora de decidir si recomiendan o no invertir en las acciones de una empresa. A su vez, tanto la percepción de la integridad de una empresa como las recomendaciones de los analistas tienen un impacto en las variaciones de los precios de las acciones.
Keywords: Reputación digital; Reputación corporativa; Ética y negocios; Integrity of governance; Corporate reputation; Transparency; Ethical behavior; Financial analyst recommendations; Daily returns